2021
DOI: 10.3389/fped.2021.706323
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk in Children With Chronic Kidney Disease: Impact of Apolipoprotein C-II and Apolipoprotein C-III

Abstract: Cardiovascular disease (CVD) is an evolving process that begins in the early stages of chronic kidney disease (CKD) in children. Several surrogate markers, such as ambulatory blood pressure monitoring (ABPM), left ventricular (LV) mass, and arterial stiffness assessment, allow for the early detection of subclinical CVD in pediatric CKD. Four groups of plasma samples (n = 3/group) from congenital anomalies of the kidney and urinary tract (CAKUT), as well as non-CAKUT patients with or without BP abnormalities, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…This is in line with prior work revealing that certain CVD risk markers already appear in children with early stages of CKD, for example, abnormalities in ABPM [ 6 , 8 , 10 , 11 , 16 ]. Although the severity of CKD was reported to be associated with high PWV and LV mass [ 8 ], we observed that these CV markers were not different between the two groups classified by the presence or absence of CAKUT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with prior work revealing that certain CVD risk markers already appear in children with early stages of CKD, for example, abnormalities in ABPM [ 6 , 8 , 10 , 11 , 16 ]. Although the severity of CKD was reported to be associated with high PWV and LV mass [ 8 ], we observed that these CV markers were not different between the two groups classified by the presence or absence of CAKUT.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, proteomics research has been broadly employed to identify protein biomarkers in many diseases [ 15 ]. Our previous study using a proteomic approach identified 20 differentially expressed proteins between CKD children with CAKUT or non-CAKUT and with or without ABPM abnormalities [ 16 ]. Our findings identified pregnancy zone protein (PZP), which will be validated in the current study to elucidate its association with CV risk in CKD children.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, children with CKD stages 2–4 had a higher plasma apolipoprotein II (ApoC-II) level than those with CKD stage 1. Additionally, ApoC-II was correlated with LVH and an abnormal ABPM profile [ 114 ]. In a consequent study, another proteomic biomarker complement factor H (CFH) and related proteins were studied in 102 children with CKD stages 1–4 [ 115 ].…”
Section: Cardiovascular Risks and Biomarkers In Pediatric Ckdmentioning
confidence: 99%
“…Combined with mass spectrometry, isobaric tags for relative and absolute protein quantification (iTRAQ) have been valuable in discovering potential protein biomarkers [ 8 ]. Our previous study using the iTRAQ technique identified several potential proteins expressed differentially between children with CKD with or without ABPM abnormalities, including complement factor H (CFH), CFH-related protein-2 (CFHR2), and CFH-related protein-3 (CFHR3) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CFHR proteins can be divided into two groups according to dimerization or not, as circulating in plasma: CFHR2 existing in dimeric form belongs to group 1, while group 2, including CFHR3, is oligomeric [ 12 ]. Considering the competition between CFHRs and CFH for binding to C3b, as described in [ 9 ], we assumed that simultaneous analysis of CFH, CFHR2, and CFHR3 might provide more information to reflect the homeostasis of the complement system.…”
Section: Introductionmentioning
confidence: 99%